Model Keamanan Data Berbasis Blockchain pada SIG untuk Monitoring Pelayanan Keperawatan Gerontik - Edi Iskandar; Sri Setyowati; Edy Prayitno; Parmadi Sigit Purnomo (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2026)
The adoption of Geographic Information Systems (GIS) in healthcare services, particularly location-based gerontological nursing, has increased significantly. However, conventional systems typically rely on centralized architectures that are vulnerable to data tampering and unauthorized access. This study aims to develop and evaluate a blockchain-based data security model integrated with GIS for monitoring gerontological nursing services. A simulation-based approach was employed to design a multi-layer architecture consisting of a GIS layer, blockchain layer, and application layer. The proposed model was evaluated using data integrity, attack detection, and system performance metrics. The results demonstrate that the model achieved 100% data integrity and an average attack detection rate of 99.2%, substantially outperforming conventional systems, which achieved only 70.3%. Although the integration of blockchain introduced additional latency, the performance remained within acceptable operational limits. This study contributes to the advancement of secure GIS–blockchain integration for location-based elderly care services and provides a replicable simulation framework for system evaluation. The findings suggest that the proposed model has strong potential for implementation in homecare services and community healthcare facilities to enhance data security, transparency, and trustworthiness.